THE UNIVE,RSITY OF BENGHAZI FA CUL TY OF ARTS THE FIRST GEOGRAPHICAL CONFERENCE ( THE GEOGRAPHY OF LIBYA ) - Goud , Dr. G. H. Goud (مجلة كلية الاداب, 1975)
In 1973 our colleague Dr. Mansour el-Kikhia, the former Dean of the Faculty of Arts proposed that a Conference on the Geography of Libya be organised. The time was ripe for his proposal. The conference aimed at studying the several aspects of the Geography of Libya through field-research. All these studies will he published in a special volume to facilitate their discussion and maximise their benefits. It was felt that a scientific conference would provide a basis for, and a stimulus to further research. It is to he hoped that the students of Geography and graduates will he inspired to take the lead in this research. Letters were sent out to as many persons known to have an interest in the Geography of Libya, inquiring as to their interest in participating in a con£ erence to be held in March 1975. The response to this initial inquiry was encouraging. The University covered all expenses regarding accommodation and transportation during the field-work and during stay to attend the conference, as well as the round-trip travelling expenses. Geographers of 8 nationalities came to Benghazi to present their contributions. I should like to take this opportunity, to thank the 29 authors who presented the papers, for their effort, which made the conference succeed so well in its stated purpose. The meetings were held in an Auditorium of the Faculty of Arts, Benghazi on March 15 to 25, 1975. Soci'al functions sponsored by the Minister of Education and two field trips to the Kufra Oases and Jahal al-Akhdar rounded out the program.